2015 Project Progress Report : Biodiversity and Its Conservation in the Satsunan Islands - Suzuki, Eizi, editor; Kawai, Kei, editor; Yamamoto, Sota, editor (Kagosima, Japan : Kagoshima University Research Center, 2016)
Includes bibliographical references.